Entrepreneurship Education and Academic Support Influence Students' Entrepreneurial Intention with Parental Role as Moderator - Revaldi Tegar Bhaskara; Komala Inggarwati (Jurnal Manajemen dan Kewirausahaan, 2023)
This study aims to examine the influence of entrepreneurship education and academic support on student entrepreneurship intentions, taking into account the moderating role of parents. The explanatory research approach was used to explain the relationships between variables and to test the hypotheses. The study’s population consists of 273 undergraduate Management students of FEB UKSW who joined in 2019. A sample of 159 students was selected using simple random sampling. The findings revealed that entrepreneurship education has a positive effect on student entrepreneurial intentions, and the role of parents with entrepreneurial backgrounds has a moderating effect that amplifies the effect of entrepreneurship education on student entrepreneurial intentions. Meanwhile, academic support is not a driver of the emergence of student entrepreneurial interest, thus other factors that may contribute to student entrepreneurial interest in the context of higher education must be investigated further.